Ouvrières agricoles et conventions collectives : de la discrimination à la reconnaissance ? (1950-2018) - Jean-Louis Escudier (Revue de la Régulation)
This article presents the long term evolution of employment and wages of the female farm workers in collective labor agreements concluded in France after the law of February 11th, 1950. The first part, focused on the genesis of this long process of institution of the agricultural collective labor agreements, is dedicated on examination of the modalities of integration of the agricultural jobs considered as “traditionally feminine” in the lists of jobs, in particular the substitution of a unique hierarchical scale to scales of jobs differentiated according to gender. In the second part, we appreciate the degree of consideration of feminine skills, in particular the treatment reserved for the farm maid, and we try to identify the least discriminating collective labor agreements for female farm workers. The third part, focused on the last fifteen years, analyzes the renewal of the discriminations according to gender from which still suffer the female farm workers in a context of severe collapse of the wage hierarchies.